(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, an experimental investigation carries out on poly-crystalline photovoltaic (PV) system for performance enhancement with the help of a thin acrylic sheet (thickness- 2 mm). There are three types of systems used under this experimental setup as (i) PV module under normal conditions/ without sheet (ii) PV module under the triangular shape of the transparent sheet (iii) PV module under rectangular shape transparent sheet. The performance analysis of all three systems has been monitored in terms of open-circuit voltage, short circuit current, power, efficiency. Simultaneously, a statistical measurement approach of sun irradiation with constant temperature is carried out during the single day experimental study. The performance of the (Triangular shaped transparent sheet) TSTS configuration found superior which provide 22.064 Watt power at 12 am, whereas (Rectangular shaped transparent sheet) RSTS configuration provide 20.4 W at the same time. The TSTS configuration provides 1.12A short circuit current at 12 am, whereas RSTS configuration provides 1.02A short circuit current at the same time. The TSTS configuration provides 8.92% better value. The TSTS configuration provides 20V open-circuit voltage at 12 am, whereas RSTS configuration provides 19.8V open-circuit voltage at the same time. The TSTS configuration provides 1% higher value. So that the TSTS configuration provides the maximum output of the solar PV panel.